The polymorphisms of genes involved in DNA methylation in patients with malignancies from West Ukraine - Dmytruk, I.M.; Makukh, H.V.; Thyrkus, M.Y.; Kitsera, N.I. (Вiopolymers and Cell, 2016)
Aim. To determine a potential role of single-nucleotide polymorphisms in the genes involved in the DNA methylation process (MTHFR, MTR, TYMS) in the breast cancer risk and risk of leukemia in a case-control study from West Ukraine. Methods. Genotyping of MTHFR 677 C>T, MTR 2756 A>G and TS 3R2R, TS 3RG>C was performed in 60 patients with leukemia, 90 patients with breast cancer and in 100 persons from a control group. The molecular-genetic analysis was performed by Polymerase Chain Reaction and Restriction Fragment Length Polymorphism analysis. A statistical analysis was conducted by Chi-square tests and odds ratio (OR) calculation. Results. We did not observe any signiﬁcant difference in genotype frequencies of the MTHFR and TYMS polymorphisms between the cases and controls. The MTR 2756AA genotype frequency was significantly higher in the patients with breast cancer vs control (0.67 vs 0.50, p = 0.02) and the difference between the patients with leukemia and the control group was not statistically significant. The increased risk of breast cancer development was associated with the MTR 2756AA genotype (OR = 2.00, CI – 95 %:1.11–3.60) and the MTR 2756A allele (OR = 1.75, CI–95 %:1.08–2.84). Conclusions. Our findings show that West Ukrainian inhabitants carrying at least one MTR 2756A allele have a significantly increased risk of breast cancer.